MicroRNA-34a Inhibits Osteoblast Differentiation and In Vivo Bone Formation of Human Stromal Stem Cells. (17th March 2014) - Chen, Li; HolmstrØm, Kim; Qiu, Weimin; Ditzel, Nicholas; Shi, Kaikai; Hokland, Lea; Kassem, Moustapha
Abstract: Osteoblast differentiation and bone formation (osteogenesis) are regulated by transcriptional and post-transcriptional mechanisms. Recently, microRNAs (miRNAs) were identified as novel key regulators of human stromal (skeletal, mesenchymal) stem cells (hMSC) differentiation. Here, we identified miRNA-34a (miR-34a) and its target protein networks as modulator of osteoblastic (OB) differentiation of hMSC. miRNA array profiling and further validation by quantitative RT-PCR revealed that miR-34a was upregulated during OB differentiation of hMSC, and in situ hybridization confirmed its OB expression in vivo. Overexpression of miR-34a inhibited early commitment and late OB differentiation of hMSC in vitro, whereas inhibition of miR-34a by anti-miR-34a enhanced these processes. Target prediction analysis and experimental validation confirmed Jagged1 (JAG1), a ligand for Notch 1, as a bona fide target of miR-34a. siRNA-mediated reduction of JAG1 expression inhibited OB differentiation. Moreover, a number of known cell cycle regulator and cell proliferation proteins, such as cyclin D1, cyclin-dependent kinase 4 and 6 (CDK4 and CDK6), E2F transcription factor three, and cell division cycle 25 homolog A were among miR-34a targets. Furthermore, in a preclinical model of in vivo bone formation, overexpression of miR-34a in hMSC reduced heterotopic bone formation by 60%, and conversely, in vivo bone formation was increased by 200% in miR-34a-deficient hMSC. miRNA-34a exhibited unique dual regulatory effects controlling both hMSC proliferation and OB differentiation. Tissue-specific inhibition of miR-34a might be a potential novel therapeutic strategy for enhancing in vivo bone formation. Stem Cells   2014;32:902–912